Estimating Default Frequencies and Macrofinancial Linkages in the Mexican Banking Sector - Souto, Marcos (IMF Working Papers; Working Paper ;, 2009)
The credit risk measures we develop in this paper are used to investigate macrofinancial linkages in the Mexican banking system. Domestic and external macro-financial variables are found to be closely associated with banking soundness. At the aggregate level, high external volatility and domestic interest rates are associated with higher expected default probability. Though results vary substantially across individual banks, domestic activity and U.S. growth, and higher asset prices, are generally associated with lower credit risks, while increased volatility worsens credit risks. The expected default probability is also found to be a leading indicator of traditional financial stability indicators.